2022
DOI: 10.3389/fped.2022.886727
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Non-invasive Ventilation in Children With Down Syndrome: A Systematic Review

Abstract: ContextChildren with Down syndrome are at risk for obstructive sleep apnea, which may not be resolved by adenotonsillecotmy, as well as other respiratory disorders that may impact breathing during sleep. Long-term non-invasive ventilation, including continuous and bilevel positive airway pressure delivery, is an alternate treatment strategy.ObjectiveTo assess the use and outcomes of long-term non-invasive ventilation in children with Down syndrome including comparison to other children using long-term non-inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Additional studies reported no difference in adherence in children with and without impaired cognition as well as higher rates of never establishing LT-NIV use in children with DS (O'Donnell et al, 2006;Amaddeo et al, 2018). Studies exclusively on children with DS support the potential for high adherence as well as adherence rates that are typical of children using LT-NIV (Hudson et al, 2022). The current study shows adherence rates are lower in children with DS though not out of keeping with rates reported in other cohorts of children using LT-NIV.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additional studies reported no difference in adherence in children with and without impaired cognition as well as higher rates of never establishing LT-NIV use in children with DS (O'Donnell et al, 2006;Amaddeo et al, 2018). Studies exclusively on children with DS support the potential for high adherence as well as adherence rates that are typical of children using LT-NIV (Hudson et al, 2022). The current study shows adherence rates are lower in children with DS though not out of keeping with rates reported in other cohorts of children using LT-NIV.…”
Section: Discussionmentioning
confidence: 95%
“…For children with DS, up to 55% go on to use LT-NIV (including continuous positive airway pressure, CPAP, and bilevel positive airway pressure, BPAP) after incomplete resolution of OSA after surgery (Shete et al, 2010;Dudoignon et al, 2017). In a systematic review of LT-NIV use in children with DS, children with DS made up 18% of children using LT-NIV across 20 studies (Hudson et al, 2022). This is in keeping with a population study of LT-NIV use in children that reported 18% of children using LT-NIV were children with DS (Castro-Codesal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Adherence to long-term continuous or bilevel pressure support in this population can be difficult comparable to other children. 2 However, there is a paucity of longitudinal data examining this within this cohort.…”
Section: P3 Longitudinal Outcomes Of Non-invasive Respiratory Support...mentioning
confidence: 93%
“…1 Hannah Williams*, 1 Sakina Birdseye-Dastagir, 1 Alex Thomas, 1,2 Hui-Leng Tan, Introduction Obstructive sleep disordered breathing (SDB) is highly prevalent in children with Trisomy 21 (T21). 1 Adherence to long-term continuous or bilevel pressure support in this population can be difficult comparable to other children.…”
Section: P3 Longitudinal Outcomes Of Non-invasive Respiratory Support...mentioning
confidence: 99%